EVALUASI PELAKSANAAN SUPERVISI MANAJERIAL KEPALA UNIT PELAKSANA TEKNIS DINAS PENDIDIKAN DAN KEBUDAYAAN KECAMATAN TAPUNG HULU - Pharada Kresna; Zulfan Saam; Sudirman AS (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2019)
Managerial Supervision Head of Technical Implementation Unit of Education and Culture Office of Tapung Hulu Sub-district has not been maximal in supervising and supervising in the preparation and development of school-level curriculum. Managerial Supervision Head of Technical Implementation Unit of Education and Culture Office of Tapung Hulu District does not supervise and develop curriculum development. Head of UPTD does not coordinate in preparing School development plan (RPS). Preparation of Annual School Activity Plan (RKTS). As well as the School Revenue and Expenditure Budget Plan (RAPBS). Managerial Supervision Head of Technical Implementation Unit of Education and Culture Office of Tapung Hulu Sub-district has not done any assistance in preparing school curriculum, School development plan (RPS). Preparation of Annual School Activity Plan (RKTS). As well as the School Revenue and Expenditure Budget Plan (RAPBS). Managerial Supervision Head of Technical Implementation Unit of Education and Culture Office of Tapung Hulu Sub-district related to the result has not coordinated with the Principal in preparing the School Development Plan (RPS)